COVID-19 pandemic and alcohol consumption: Impacts and interconnections - Calina, Daniela (Toxicol Rep, 2021)
Alcohol consumption is associated with multiple diseases and might contribute to vulnerability to SARS-CoV-2 infection. It can also catalyze exacerbations of mental and organic illnesses and predispose to behaviors with an increased risk of infection, severity of disease but also independently of sociopathic behavior and violence. Globally, millions of premature deaths from excessive alcohol consumption occur each year. This paper discusses the effects of increased alcohol consumption and the most important consequences on the health of the population during the social isolation and lockdown during current COVID-19 pandemic.